2009
DOI: 10.1179/crn.2009.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mandibular Deviation on Brain Activation During Clenching: An fMRI Preliminary Study

Abstract: Using functional magnetic resonance imaging (fMRI) in eight healthy human subjects, the present study measured blood oxygenation level-dependent (BOLD) signals during clenching in a malocclusion model, using a custom-made splint that forced the mandible to a retrusive position and a splint of no modification for control, and compared the results to the BOLD signals during the corresponding resting conditions. An individual visual analog scale (VAS) score was also examined during clenching to evaluate the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 15 publications
1
30
1
Order By: Relevance
“…Otsuka et al measured BOLD signals during clenching in a malocclusion model using a custom-made splint in humans and reported that malocclusion affects emotion-related neuronal processing in the brain, such as in the anterior cingulate cortex and amygdala 61) . The occlusal disharmony-induced changes in the hippocampus are due largely to stress responses.…”
Section: Effects Of Occlusal Disharmony On Cognitive Functionmentioning
confidence: 99%
“…Otsuka et al measured BOLD signals during clenching in a malocclusion model using a custom-made splint in humans and reported that malocclusion affects emotion-related neuronal processing in the brain, such as in the anterior cingulate cortex and amygdala 61) . The occlusal disharmony-induced changes in the hippocampus are due largely to stress responses.…”
Section: Effects Of Occlusal Disharmony On Cognitive Functionmentioning
confidence: 99%
“…Brain function was analyzed before orthodontic treatment with and without the occlusal splint and after orthodontic treatment using exactly the same procedure as in a previous fMRI study [11]. Briefly, a 1.5-T Horizon MRI scanner (PHILIPS, InteraAchiva) first produced functional images (T2*-weighted) and then an The SPM5 software (Wellcome Department of Cognitive Neurology, London, UK) was used to correct for inadvertent head motion.…”
Section: Functional Magnetic Resonance Imaging Analysis For Brain Funmentioning
confidence: 99%
“…A human study also showed that mastication and teeth clenching prevent stress-induced amygdala activity in the brain [14]. Recently, it was reported that experimental posterior displacement of the mandible induced significant activity in the limbic system [11] suggesting that mandibular displacement due to malocclusion, such as unstable intercuspation or poor posterior vertical support, may be associated with somatic symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] These studies indicate that occlusal dysfunction affects the stress response via brain function and leads to non-oral health problems. Experiments with human subjects have shown that posterior mandibular displacement significantly activates the limbic system, 5 indicating that occlusal dysfunction causes various somatic symptoms. Functional MRI is a useful noninvasive tool for testing specific hypotheses regarding the anatomical regions that process sensory and motor signals in the brain.…”
mentioning
confidence: 99%